Ambiguities of xenophobia in a border town: inner city informal traders and Ekasi shopkeepers in the city of East London, South Africa. Issue 2 (2nd April 2020) - Connor, Teresa K.; Charway, Fred
ABSTRACT: This paper explores the livelihoods, experiences and identities of immigrant informal traders and shopkeepers in the Buffalo City Metropolitan area, which encompasses the centres of East London, Mdantsane and King Williams Town. We primarily use a socio-spatial perspective to analyse informal activity, and offer a particular perspective on how informality has encouraged a type of 'informal citizenry' among traders. We argue that informal trading has a very particular history in the region, and that East London's notoriety as a 'border city' and a regional frontier has created a fractured space, which is best expressed through the experiences of migrants and entrepreneurs. We point out that informality is a driver of economic empowerment and equality among traders, but also of xenophobia and difference.